AN ANALYSIS OF CODE MIXING AND CODE SWITCHING USED BY THE STUDENT OF NURUL HUDA ISLAMIC BOARDING SCHOOL - Ninik Indah Purnamasari; Norma Ita sholichah (English Language Teaching Journal, 2022)
This research focuses on code mixing and code switching. This research uses descriptive qualitative, where this research wants to explain the data with real results. The results of this study have two discussions. First, the form of code mixing from Javanese to Indonesian, from Indonesian to Javanese and from Javanese to English. Then, the form of transfer found by the researcher is from Javanese to Indonesian and from Indonesian to Javanese. Second, the factors that cause code mixing are: a). Santri understand the language spoken by the interlocutor but cannot express it, b). happens intentionally or unintentionally, c). because they are used to using code mixing when speaking, d). as a form so that they can talk using code mixing. In addition, the factors that cause code switching are: a). Speaker, b). interlocutor, c). the presence of other people.